Alzheimer's diagnosis beyond cerebrospinal fluid: Probe-Free Detection of Tau Proteins using MXene based redox systems and molecularly imprinted polymers - Arjun, Ajith Mohan; Deshpande, Sudhaunsh; Dunlop, Tom; Norman, Beth; Oliviera, Daniela; Vulpe, Georgeta; Moreira, Felismina; Sharma, Sanjiv (Biosensors and bioelectronics. X, 2024)
Phosphorylated Tau proteins are promising biomarkers for the diagnosis and prognosis of Alzheimer's disease. This study presents a novel voltametric sensor using a vanadium MXene polydopamine (VxPDA) redox active composite and a Tau-441-specific polyaniline molecularly imprinted polymer (PANI MIP) for the sensitive detection of Tau-441 in interstitial fluid (ISF) and plasma. The VxPDA/PANI MIP sensor demonstrates a broad detection range of 5 fg/mL to 5 ng/mL (122 aM/L to 122 pM/L) in ISF without the use of redox mediators, with a lower limit of detection (LOD) of 2.3 fg/mL (60 aM/L). Furthermore, a handheld device utilizing this technology successfully detects Tau-441 in artificial serum with high sensitivity (5 fg/mL to 150 fg/mL (122 aM/L to 366 aM/L)) and specificity within a clinically relevant range. The rapid detection time (∼32 min) and low cost (∼£20/device) of this sensor highlight its potential for minimally invasive, early AD diagnosis in clinical settings. This advancement aims to facilitate a transition away from invasive cerebrospinal fluid (CSF)-based diagnostic techniques for AD. •Novel Vanadium MXene-Based Sensor enables probe-free biomarker detection.•Performance validated in interstitial fluid and artificial serum.•Ultrasensitive Detection of 122 aM/L of Tau-441.•Rapid (∼32 min) Tau-441 detection in serum for ∼£20.•Simplified, accessible early Alzheimer's diagnostics.